Penggunaan Model Kohonen-Self Organizing Maps untuk Penentuan Tingkat Keberlanjutan Pembangunan di Wilayah Kabupaten Bantul - Kurniawan, Andri; Savira, Maulidia; Windari, Endah (Universitas Pendidikan Ganesha, 2025)
The diversity of development intensity and variation in regional characteristics, as well as various patterns of relationships between components, indicate the complexity of the study of the level of development sustainability in a region. To understand this complexity, a model is needed to provide an overview of the characteristics of regional development sustainability and the patterns of relationships that occur. The development of this model needs to be carried out through the development of an